Community Participation in Transect on Development Planning - Mustanir, Ahmad; Yasin, Akhmad (Jurnal Ilmiah Ilmu Administrasi Publik, 2018)
This research is to know the use of Transect method as participatory planning method in finding of potency, problem visually and practice to the participatory development planning in Tonrong Rijang village, Baranti sub-district, Sidenreng Rappang regency. Additionally, by understanding the goal so, it can contribute as one of the methods which can be used in participatory development planning. The method can also help researchers in increasing their understanding and knowledge toward participatory development planning. The research methods in this study were observation, interview and literature study related to the research. Then, research technique in this study was Interactive Model of Analysis. This technique in analyzing qualitative data was conducted interactively and continuously to the end. Collection data, display data and conclusion drawing/verifying were activities in analyzing the data. The result of this research showed that Transect was a new thing in the society especially in a development planning. Interaction process in society which occurred in development planning was similar with Transect. This activity was similar when doing an accompaniment to other people in a specific event. However, dominant activity only happened in a deliberation which has been commonly conducted in a tradition.